Highly Scalable, Wearable Surface‐Enhanced Raman Spectroscopy. Issue 17 (22nd June 2022) - Liu, Limei; Martinez Pancorbo, Pablo; Xiao, Ting‐Hui; Noguchi, Saya; Marumi, Machiko; Segawa, Hiroki; Karhadkar, Siddhant; Gala de Pablo, Julia; Hiramatsu, Kotaro; Kitahama, Yasutaka; Itoh, Tamitake; Qu, Junle; et al.
Abstract: The last two decades have witnessed a dramatic growth of wearable sensor technology, mainly represented by flexible, stretchable, on‐skin electronic sensors that provide rich information of the wearer's health conditions and surroundings. A recent breakthrough in the field is the development of wearable chemical sensors based on surface‐enhanced Raman spectroscopy (SERS) that can detect molecular fingerprints universally, sensitively, and noninvasively. However, while their sensing properties are excellent, these sensors are not scalable for widespread use beyond small‐scale human health monitoring due to their cumbersome fabrication process and limited multifunctional sensing capabilities. Here, a highly scalable, wearable SERS sensor is demonstrated based on an easy‐to‐fabricate, low‐cost, ultrathin, flexible, stretchable, adhesive, and biointegratable gold nanomesh. It can be fabricated in any shape and worn on virtually any surface for label‐free, large‐scale, in situ sensing of diverse analytes from low to high concentrations (10–10 6  × 10 −9 m ). To show the practical utility of the wearable SERS sensor, the sensor is tested for the detection of sweat biomarkers, drugs of abuse, and microplastics. This wearable SERS sensor represents a significant step toward the generalizability and practicality of wearable sensing technology. Abstract : Highly scalable, wearable surface‐enhanced Raman spectroscopy based on an easy‐to‐fabricate, low‐cost, ultrathin, flexible, stretchable, adhesive, and biointegratable gold nanomesh is demonstrated in this study. It can be fabricated in any shape and worn on virtually any surface for label‐free, large‐scale, in situ sensing of diverse analytes from low to high concentrations.